2022
DOI: 10.1155/2022/6709787
|View full text |Cite
|
Sign up to set email alerts
|

Brown Rice Germ Integrity Identification Based on Deep Learning Network

Abstract: For the quality inspection of brown rice, the segmentation of connected brown rice and the identification of germ integrity are very important. However, there is no better traditional algorithm to achieve better segmentation and recognition results. This paper improves the brown rice (BR) segmentation algorithm based on background skeleton. The candidate matching points are obtained by the background skeleton method, and the optimal matching points are found by the ant colony algorithm. Experimental results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Deep learning has been widely used in foods and agriculture in recent years [7,8], and image recognition of plants has received a lot of attention from researchers. Following this trend, nondestructive age recognition of the tangerine peel contributes to the development of the intelligent tangerine peel industry.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has been widely used in foods and agriculture in recent years [7,8], and image recognition of plants has received a lot of attention from researchers. Following this trend, nondestructive age recognition of the tangerine peel contributes to the development of the intelligent tangerine peel industry.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic identification method of pipeline weld defects based on deep learning [2][3][4][5][6][7][8][9][10][11][12] can effectively solve the problems of time-consuming labor and low efficiency of manual film evaluation. Liu Han et al [13] used convolutional neural network to automatically extract deep-level features of defects, which not only realized automatic classification, but also improved the time-consuming and laborious problem of manual feature extraction; Jiang Hongquan et al [14] used random forest algorithm to improve the feature selection method of CNN model, and improved the parameter learning ability of traditional CNN method; Daniel Bacioiu et al [15] used the fully connected network architecture combined with convolutional neural network to identify 6 types of defects, 4 types of defects, and 2 types of defects, with accuracy rates of 70%, 85%, and 95%, respectively, it can be seen that the classification accuracy of the model decreases significantly in the face of multiple defects.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Li [ 23 ] improved Inception-v3 by introducing fine-grained classification to learn local features of rice and to identify the integrity of the rice germ. Li et al [ 24 ] refined the Inception-v3 model to detect the integrity of the germ with the addition of mutual channel loss and mlpconv. Li et al [ 25 ] identified rice germ integrity based on the EfficientNet-B3 model with the introduction of the double attention network (DAN).…”
Section: Introductionmentioning
confidence: 99%